Adoption of the Plea Bargaining Concept to Improve Judicial Efficiency During the Covid-19 Outbreak - Herawan, Wahyu Nandang; Sihotang, Natalia (Law Research Review Quarterly, 2021)
Plea Bargaining can be interpreted as a statement of guilt from a suspect or defendant. Plea Bargaining is widely embraced in countries that adhere to the Common Law legal system. Plea Bargaining developed in the common law legal system has inspired the emergence of mediation in the practice of justice based on criminal law in the Netherlands and France, known as Ã¢â‚¬Å“transactieÃ¢â‚¬Â. This paper is intended to analyze the concept of plea bargaining on improving judicial efficiency during the Covid-19 Pandemic in Indonesia. This research confirmed that plea Bargaining is categorized as an attempt to resolve outside the court and its users are also based on certain reasons. Whereas the presence of the concept of a special route is also a concern if we see that the defendantÃ¢â‚¬â„¢s confession of guilt can be reinstated as the basis for a judge to issue a verdict. The purpose of this paper is to find out and analyze the application of plea bargaining in the midst of the global Covid-19 pandemic in Indonesia.